1972
DOI: 10.1042/cs0430481
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Adrenergic Nervous System and Renin during Adaptation to Upright Posture: A Possible Role for 3,4-Dihydroxyphenethylamine (Dopamine)

Abstract: S U M M A R Y1. The role of the adrenergic nervous system in the regulation of plasma renin activity was investigated in fourteen healthy volunteers. Special attention was devoted to 3,4dihydroxyphenethylamine (dopamine) because this amine is not only a precursor of noradrenaline, but also a catecholamine with its own functions. The adrenergic nervous system was activated by a change of posture because this offers a simple and reproducible stimulus; its effects were studied during a normal diet and also after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…Low doses of dopamine cause renal vasodilatation and increase the rates of urinary Na+ and water excretion in man (McDonald, Goldberg, McNay & Tuttle, 1964), and in the dog (Meyer, McNay & Goldberg, 1967). The urinary excretion of dopamine parallels normal changes in salt and water excretion in man (Cuche, Kuchel, Barbeau, Boucher & Genest, 1972;Alexander, Gill, Lovenberg, Yamabe & Keiser, 1972) and in the rat (B. Woodward, personal communication). Urinary Na+ excretion decreases when the synthesis of endogenous dopamine is inhibited (Ball & Lee, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Low doses of dopamine cause renal vasodilatation and increase the rates of urinary Na+ and water excretion in man (McDonald, Goldberg, McNay & Tuttle, 1964), and in the dog (Meyer, McNay & Goldberg, 1967). The urinary excretion of dopamine parallels normal changes in salt and water excretion in man (Cuche, Kuchel, Barbeau, Boucher & Genest, 1972;Alexander, Gill, Lovenberg, Yamabe & Keiser, 1972) and in the rat (B. Woodward, personal communication). Urinary Na+ excretion decreases when the synthesis of endogenous dopamine is inhibited (Ball & Lee, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…However, a role for this catecholamine in the physiological control of sodium excretion has not been established. Cuche et al (1972) showed that when normal subjects stand there is an increase in urinary adrenaline and noradrenaline, but a fall in urinary dopamine and sodium. They also found a correlation between urinary sodium and dopamine in the supine and upright postures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both PNE and dopamine are increased concomitantly in response to sodium depletion, 15 but several other conditions such as upright posture, isometric or treadmill exercise, or exposure to cold are associated with elevated sympathetic activity while blood levels of dopamine remain unchanged. 24 Moreover, the response of urinary dopamine excretion to orthostasis and changes in salt intake is discordant with that of plasma and urinary norepinephrine, 25 ' M suggesting an inverse relationship between the sympathetic nervous system and the dopaminergic axis at the renal level. Plasma epinephrine was unchanged during norepinephrine infusion in both study groups and under placebo conditions as well as following diuretic administration.…”
Section: Discussionmentioning
confidence: 88%